The potential of using grapefruit peel as a natural support for yeast immobilization during beer fermentation - Estela-Escalante, Waldir D.; Perez-Escalante, Jimy J.; Fuentes-Navarro, Eduardo L.; Pinillos-Miñano, Ricardo M. (2020)
The potential use of grapefruit peel as support material for yeast immobilization during beer fermentation was evaluated. After conditioning, FTIR analysis revealed a higher quantity of methoxy (–OCH3) groups, suggesting that lignin is the major component of the support. Cell adhesion onto the conditioned support in 12°Plato laboratory malt wort was evaluated, observing a maximal cell adhesion (2.25 · 109 cells/gram of dried support) at 20 h of cultivation, remaining almost constant in the subsequent time points. Evaluations of the fermentative behaviour of the biocatalyst at 15±0.5 °C in a 14°Plato laboratory malt wort indicated good stability in terms of physical integrity (confirmed by SEM observation). The fermentation time was shortened to four days, and the rates of reducing sugar consumption and ethanol production were improved when compared to fermentations carried out with free suspended cells. These results show a promising potential of grapefruit peel as support material in beer fermentation.
Bibliografija: 42 jed.
Summary.
Keywords: Grejpfrut -- Kora grejpfruta -- Kvasac -- Imobilizirani kvasac -- Alkoholno vrenje -- Pivo